Analysis and modeling of delamination factor in drilling of woven kenaf fiber reinforced epoxy using Box Behnken experimental design - Mokhtar, Suhaily; Che Haron, Che Hassan; A. Ghani, Jaharah; Mohd Ali, Afifah; Mohd Khairussaleh, Nor Khairusshima (IOP Publishing, 2018)
In this research study, it presents a comprehensive mathematical model for correlating the influences of drilling parameters on the delamination factor during the drilling of woven kenaf fiber reinforced epoxy composite laminates using the Box Behnken experimental design. The purpose of this study is to investigate the influence of drilling parameters such as cutting speed, feed rate and drill sizes on the delamination produced when drilling woven kenaf reinforced epoxy composite using the non-coated HSS drill bits. The damage generated on the woven kenaf reinforced epoxy composite laminates were observed both at the entrance and exit surface during the drilling operation. The experiments were conducted according to the Box Behnken experimental designs.